Innovations in Epic Studies by Lauri Honko - Pekka Hakamies (Approaching Religion, 2014)
This article aims at tracing the roots of the theoretical concepts developed by Lauri Honko in his research on epic: what were his main sources in theoretical thinking, how did he apply and develop concepts formulated by authors such as Albert Lord, and what were his own innovations. This article aims also at relating Honko’s thinking to other relevant theoretical perspectives, but which he more or less rejected or ignored in his writings.